2001
DOI: 10.1099/00207713-51-2-311
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Xylella fastidiosa strains from different hosts, based on 16S rDNA and 16S-23S intergenic spacer sequences.

Abstract: The phylogenetic relationships of Xylella fastidiosa strains isolated from different hosts, including citrus trees, coffee, grapevine, plum and pear, were inferred by sequence analysis of the 16S rDNA and 16S-23S intergenic spacer region. A high level of similarity (97 1-100 %) was found in the 16S rDNA of the Xylella fastidiosa strains. The 16S-23S region showed a higher level of variation, with similarity values ranging from 79 8 to 100 %. Two tRNAs (tRNA Ala and tRNA Ile ) were encountered within the spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 27 publications
(32 reference statements)
6
29
1
1
Order By: Relevance
“…The subdivision of Xf strains into at least two distinct groups is in accord with previous observations (Chen et al 2000;Hendson et al 2001;Mehta and Rosato 2001), but even inside each group, a considerable degree of variation can be observed. The citrus group bears duplicated regions not observed in the coffee strain.…”
Section: Genome Research 575supporting
confidence: 77%
See 1 more Smart Citation
“…The subdivision of Xf strains into at least two distinct groups is in accord with previous observations (Chen et al 2000;Hendson et al 2001;Mehta and Rosato 2001), but even inside each group, a considerable degree of variation can be observed. The citrus group bears duplicated regions not observed in the coffee strain.…”
Section: Genome Research 575supporting
confidence: 77%
“…Within group 2, the almond/grape strains display a similar profile, whereas elm and plum II isolates are nearly identical to each other, contrasting with plum I. Independent studies found strain plum I to have a closer phylogenetic relationship with the citrus-coffee strains than with others (da Costa et al 2000;Mehta and Rosato 2001). This finding is in accord with geographic distribution, as plum I was originally obtained from a diseased tree in the southern region of Brazil, being the first Xf isolate obtained in that country (French and Kitajima 1978).…”
Section: Genome Research 575mentioning
confidence: 99%
“…The presence of widespread recombination in the dataset and the small number of loci tested may have been important factors affecting this analysis. Similar factors may underlie contradictory results previously published on the genetic relationships among CVC and CLS X. fastidiosa isolates (29,30,42). The lack of geographical structure in the samples is not surprising.…”
Section: Discussioncontrasting
confidence: 54%
“…The grapevine-infecting variants responsible for PD are found in one group, while the citrus-infecting variants responsible for CVC are found in another (6,7,16). Initial expectations, based on geographical distributions, host diversity, differential disease symptoms, and molecular analyses, were that organisms from the three groups would be sufficiently different to support taxonomic separation at the subspecies or pathovar level (17,19,24).…”
mentioning
confidence: 99%